The Conceptual Framework for Public Sector Entities’ Managerial Accounting - KORYTNYK, L. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
In order to ensure the realization of the principles of public policy for the modernization of the budget process and accounting system, the urgent task today is to develop conceptual bases for the implementation of management accounting for public sector entities that cannot be successfully and effectively applied without building a theoretical and methodological basis. Taking into account the purpose, objectives and goals of activities of the administrators of budget funds at different levels of management, the author’s position is proposed to determine the management accounting for each of them. This made it possible to assert that for the main administrators of budget funds the management accounting is aimed at fulfilling the functions of national importance, and for the lower level administrators of budget funds – to fulfill the statutory mission and to ensure a competitive position in the public services market. Studies of scientific and methodological approaches to the definition of the subject, objects, function, tasks and principles of management accounting allowed to make proposals for the specification of the subject, systematization of objects, expanding the list of existing functions, tasks and principles of management accounting, taking into account modern requirements for informative provision of economic information the processes of activity of public sector entities and the level of their participation in the budget process. The results of the conducted research will contribute to the continuation of the formation of the basic provisions of the national accounting system, taking into account the current needs of the information management space and the peculiarities of activities and status of administrators of budget funds.